Effectiveness of mobile health for exercise promotion on cardiorespiratory fitness after a cancer diagnosis: A systematic review and meta‐analysis - Megan E. Gregory; Weidan Cao; Saurabh Rahurkar; Fadi Haroun; James C. Stock; Sanam M. Ghazi; Daniel Addison (Cancer Medicine)
Abstract Background Cancer survivors are at greater risk for cardiovascular‐related mortality. Mobile health (mHealth) is an increasingly prevalent strategy for health promotion, but whether it consistently improves cardiorespiratory outcomes after a cancer diagnosis is unknown. We sought to determine the effectiveness of mHealth fitness/physical activity interventions on cardiorespiratory fitness outcomes among cancer patients and survivors. Methods Leveraging MEDLINE/PubMed, Scopus, and ClinicalTrials.gov, we identified studies through May 2023. Included studies provided a quantitative evaluation of an mHealth intervention in a primary or secondary capacity on cardiorespiratory fitness (6‐minute walk test, VO2max, 3‐minute step test, or systolic blood pressure; or any mention of cardiac measure) and were meta‐analyzed (using a random effects model) if they were a randomized controlled trial with sufficient quantitative information. Four coders were involved in applying inclusion/exclusion criteria, coding using a standardized data extraction sheet, and assessing study quality, with each study coded by at least two. Results Of 656 articles, nine (n = 392) met systematic review inclusion criteria (mean age range 19–62 years, 71.9% female, 60.9% breast cancer). Interventions included mobile apps (k = 6), smartwatches (k = 2), or a smartwatch plus a supplemental web/mobile/tablet app (k = 1); median duration of mHealth‐use was 12 weeks. Seven (n = 341) fit criteria for meta‐analysis. mHealth was associated with improved cardiorespiratory fitness (d = 0.33; 95% CI = 0.07–0.60) compared to a control group. Relationships remained after accounting for lipid‐based outcomes (d = 0.30; 95% CI = 0.03–0.56). There was no evidence for heterogeneity or publication‐bias. Conclusions mHealth exercise interventions appear to be a viable strategy for improving cardiorespiratory fitness after a cancer diagnosis.